Imaging of Entrapment Neuropathies in the Ankle - Jo, Stephanie Y.; Khurana, Navpreet; Shabshin, Nogah (Seminars in Musculoskeletal Radiology, 2022)
Entrapment neuropathies of the ankle and foot pose a major diagnostic challenge and thus remain underdiagnosed. Recent advancements in imaging modalities, including magnetic resonance neurography (MRN), have resulted in considerable improvement in the anatomical localization and identification of pathologies leading to nerve entrapment. MRN supplements clinical examination and electrophysiologic studies in the diagnosis of neuropathies, aids in assessing disease severity, and helps formulate management strategies. A comprehensive understanding of the anatomy and imaging features of the ankle is essential to diagnose and manage entrapment neuropathies accurately. Advancements in imaging and their appropriate utilization will ultimately lead to better diagnoses and improved patient outcomes.
Keywords: magnetic resonance neurography; entrapment; neuropathy; lower extremity